The Effect of Women’s Empowerment on Unmet Needs for Family Planning in Tanzania: Analysis of 2022 Tanzania Demographic and Health Survey (TDHS) - Munawar Harun Koray; Sara Sulieman; Fatma Ahmed Said; Sudue Epaphraditus Mieh; Tanya Curry; Mary Modupe Abiona; Mansour Maulid Mshenga; Gifty Marley (BMC Public Health)
Abstract Introduction The role of women’s empowerment in reducing unmet needs for family planning (FP) has received limited attention, particularly in Tanzania. While empowerment may be key to addressing disparities in FP use, its impact on unmet FP needs remains underexplored. This study assessed the impact of women’s empowerment on unmet FP needs, using the Survey-based Women’s Empowerment (SWPER) Global Index as a measure of empowerment. Methods This cross-sectional study utilized data from the 2022 Tanzania Demographic and Health Survey (TDHS). The sample consisted of 9,000 women aged 15–49 years. Descriptive statistics summarized socio-demographic characteristics and unmet FP needs. Pearson’s chi-square test assessed associations between socio-demographic variables, empowerment domains, and unmet FP needs. Multilevel mixed-effects logistic regression analyzed the relationship between women’s empowerment and unmet FP needs, controlling for individual and community-level factors. Statistical significance was set at p < 0.05 with a 95% confidence interval, using STATA version 18 for analysis. Results The study found that 20.9% of women had unmet FP needs. Multilevel logistic regression revealed significant associations between women’s empowerment and unmet FP needs. High empowerment in social independence increased the likelihood of unmet FP needs by 41.9% (aOR = 1.42, 95% CI: 1.17–1.71), while high empowerment in decision-making reduced the odds by 17.6% (aOR = 0.82, 95% CI: 0.70–0.96). Increasing age and prior contraceptive use decreased unmet FP needs, with women aged 45–49 being 88.8% less likely to report unmet needs (aOR = 0.112, 95% CI: 0.08–0.16). Community-level education and FP knowledge were associated with lower unmet needs (aOR = 0.799, 95% CI: 0.71–0.91; aOR = 0.385, 95% CI: 0.35–0.43). Female-headed households had higher odds of unmet needs (aOR = 1.186, 95% CI: 1.02 − 1.38). Conclusion These findings emphasize the need for integrated approaches to address unmet FP needs. Policies should focus on enhancing women’s empowerment through education, improving access to reproductive health services, and addressing socio-economic disparities. Policy makers can leverage on community-level interventions to promote FP uptake and reproductive health outcomes.